2016
DOI: 10.1186/s40665-016-0015-2
|View full text |Cite
|
Sign up to set email alerts
|

Change in trade wind inversion frequency implicated in the decline of an alpine plant

Abstract: Background: Detailed assessments of species responses to climate change are uncommon, owing to the limited nature of most ecological and local climate data sets. Exceptions, such as the case of the Haleakalā silversword, can provide important insights into the complexity of biological responses to changing climate conditions. We present a time series of decadal population censuses, combined with a pair of early population projections, which together span the past 80 years of demographic history for this alpine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The most recent estimate of the total population size was roughly 40,000 plants in 2013 (Krushelnycky et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most recent estimate of the total population size was roughly 40,000 plants in 2013 (Krushelnycky et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its ecological and cultural importance and protected status, an abundance of ecological information has been collected for this species, which has revealed that its population has undergone a substantial climate‐associated decline in recent decades, principally in the lower portion of its elevational range (Krushelnycky et al. , ). Although it has been hypothesized that the lower elevation limit of Haleakalā silverswords (hereafter, silverswords) could be controlled in part by damage to the apical meristem from high temperatures (Melcher et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations